The Processing and Utilization of Hepatocyte Growth Factor/Scatter Factor Following Partial Hepatectomy in the Rat - Pediaditakis, Peter (2001)
Hepatocyte growth factor/scatter factor (HGF/SF) is a pluripotent growth factor capable of acting as a motogen, a morphogen, and a mitogen. Originally, HGF/SF was found as a blood-borne mitogen for hepatocytes and has since been determined to be very important in liver repair. Previous studies have established that HGF/SF must be proteolytically cleaved to elicit its effects. After liver injury by toxins such as carbon tetrachloride or after surgical resection, partial hepatectomy (PHX), HGF/SF concentrations increase in the blood. The aims of this study were to examine (1) which form of HGF/SF is present in the normal liver, (2) which form is present in the regenerating liver after PHX, and (3) if the HGF/SF used after PHX is derived from existing liver reservoirs. Both single-chain HGF/SF and active two-chain HGF/SF are present in normal liver, with the former being the dominant form. After PHX, the liver can be described as having two phases with regard to the use of endogenous HGF/SF. The first phase from 0 to 3 hours is the consumptive phase and is characterized by a decrease in both single-chain HGF/SF and active two-chain HGF/SF. The second phase is the productive phase. It is characterized by a pronounced reappearance of both single-chain HGF/SF as well as two-chain HGF/SF. The activation index shows a 5-fold increase over sham operations during the productive phase. The use of radiolabeled HGF/SF showed that during the first 3 hours, HGF/SF is used in part from hepatic stores. Furthermore, during the first 3 hours after PHX, only active two-chain HGF/SF is seen in the plasma.